In vitro Development of Protocorms and Regeneration through Non-Symbiotic Seed Culture of a Medicinally Important Orchid of Cymbidium aloifolium (L.) Sw. (Plant Tissue Culture and Biotechnology, 2025)
Different plant growth regulators were applied for in vitro development of protocorms, regeneration and mass multiplication using immature seeds of Cymbidium aloifolium. The germination ability and early development of protocorm-like bodies (PLBs) were evaluated on MS, ½MS, KC and VW media. In addition, different plant growth regulators, viz. BAP, Kn, NAA and IAA were used either individually or in combination with the medium. The maximum percentage of seed germination (97%) was recorded after initiation of cultures for 4-5 weeks. The highest number of protocorms was developed from germinated seeds after 5-7 weeks and seedlings were also developed after 15-16 weeks of culture initiation on MS basal medium without the phytohormones. The MS was found to be the most suitable medium for seed germination as well as seedling formation. Maximum shoot length (4.63 ± 0.56 cm) was recorded when MS medium was supplemented with BAP (1.0 mg/l) and NAA (0.5 mg/l). For root induction, ½MS medium containing NAA showed more superiority than other hormonal supplements. The highest number (5.62) of rooted plantlets and maximum root length (3.95 cm) were observed on ½MS medium containing 0.5 mg/l NAA. The well-rooted plantlets were acclimatized and successfully transferred to the pot containing soil. The protocol established under this study would be helpful for further research for the isolation of biochemical compounds for medicinal uses of this orchid and also for commercial cultivation purposes.Plant Tissue Cult. & Biotech. 35(1): 1-11, 2025 (June)